Composite Sulfur Electrode Prepared by High-Temperature Mechanical Milling for use in an All-Solid-State Lithium–Sulfur Battery with a Li3.25Ge0.25P0.75S4 Electrolyte. (20th December 2017) - Suzuki, Kota; Kato, Dai; Hara, Kosuke; Yano, Taka-aki; Hirayama, Masaaki; Hara, Masahiko; Kanno, Ryoji
Abstract: Composite sulfur electrodes are prepared by high-temperature mechanical milling (443 K) for use in all-solid-state lithium–sulfur batteries, and their structures and electrochemical properties are investigated. Composites comprising sulfur, acetylene black, and a Li3.25 Ge0.25 P0.75 S4 solid electrolyte are fabricated by planetary ball milling using a temperature-controlled system. The composite electrode exhibits a high discharge capacity of greater than 1200 mAh g −1 and a good cycle capability. As a result of high-temperature milling, composites are formed, incorporating novel structural units from the reaction between sulfur and the solid electrolyte, along with their intrinsic characteristics. Hence, high-temperature milling demonstrates promise for the fabrication of a composite electrode exhibiting high, reversible electrochemical activities for use in an all-solid-state lithium–sulfur battery. Highlights: Composite sulfur electrodes are prepared by high-temperature mechanical milling. The composite exhibited a high discharge capacity of greater than 1200 mAh g −1 . Novel structure unit forms via a reaction between thio-LISICON and sulfur. Liquid phase sulfur prevents severe decompositions of materials employed.